노인인구의 구강건강 및 치석제거 인식도 조사 - 곽정숙; Jung Suk Kwak; 우승희; Seung Hee Woo; 이재라; Jae Ra Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of the study is to investigate the awareness toward oral health and plaque removal in the elderly people in Korea. Methods: An interview method was carried out to 308 elderly people from a senior welfare facility in Mokpo, Jeonnam from May 1 to December 30, 2011 after receiving informed consents. Except 4 incomplete answers, data were analyzed using SPSS 18.0 program. The questionnaire consisted of demographical characteristics of the subjects, experience of plaque removal, recognition towards plaque removal, and correlation to systemic diseases. Results: Most of the elderly people experiences plaque removal(63.4%) and 55.9% had revisit intention. Those having plaque removal accounted for 47.8% and they had good subjective oral health recognition. Those not having plaque removal accounted for 61.8% and 61.8% having average systemic health condition and 53.3% having poor oral health recognition. The plaque removal was closely related to subjective oral health recognition. Conclusions: It is necessary to develop the preventive oral health program for the elderly people. The plaque removal in the elderly people is the most important services to prevent the systemic diseases including hypertension, arthritis, diabetes, nervous disease, and gastrointestinal diseases.